2018
DOI: 10.31849/paudlectura.v2i01.1989
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Meningkatkan Kreativitas Anak melalui Permainan Finger Painting Usia 5-6 Tahun di TK Harapan Bunda Pekanbaru

Abstract: Abstrak Kreativitas adalah kemampuan untuk menciptakan sesuatu yang baru yang berupa gagasan maupun karya nyata. Adapun tujuan dari penelitian yaitu untuk mendapatkan data perkembangan kreativitas anak  melalui permainan finger painting. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas ( PTK) . Subjek yang diambil untuk penelitian  terdiri dari 15 anak di TK Harapan Bunda. Teknik pengumpulan data dalam penelitian ini adalah melalui lembar observasi, dan dokumentasi. Teknik analisis data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Kreatifitas merupakan kemampuan untuk memberikan gagasan-gagasan baru yang dapat diterapkan dalam pemecahan masalah atau sebagai kemampuan untuk melihat hubunganhubungan baru antara unsur-unsur yang telah ada sebelumnya (Jumilah et al, 2018).…”
unclassified
“…Kreatifitas merupakan kemampuan untuk memberikan gagasan-gagasan baru yang dapat diterapkan dalam pemecahan masalah atau sebagai kemampuan untuk melihat hubunganhubungan baru antara unsur-unsur yang telah ada sebelumnya (Jumilah et al, 2018).…”
unclassified
“…The findings of this study are in line with Cahyati et al (2015), the method of playing through finger painting activities can improve fine motor skills in group B2 children of Santa Maria Singaraja Kindergarten. Another study by Jumilah et al (2018) revealed that one of the causes of the underdevelopment of children's creativity is because the application of finger painting in learning is rarely applied.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with Jumilah researcher, Sean Marta Efastri Siti Fadillah entitled "Efforts to Increase Children's Creativity through Finger Painting Games Aged 5-6 Years at Harapan Bunda Kindergarten Pekanbaru" shows a lot of improvement, between cycle I and cycle II there was a lot of improvement, So we can conclude that coloring can stimulate children's creativity, as proven by the research results obtained. Children's ability to color has increased better than before, because the teacher has given better examples and the teacher also frees the children to give colors according to the child's imagination, the teacher still directs giving colors, but the teacher gives the children the freedom to be better creative (Jumilah., 2018).…”
Section: Action Cycle II Meetingmentioning
confidence: 99%